2022
DOI: 10.3390/ph15091123
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Inhibits JAK/STAT and PI3K/Akt/ mTOR Signaling Pathways in MV4-11 and K562 Myeloid Leukemia Cells

Abstract: Constitutive activation of Janus tyrosine kinase-signal transducer and activator of transcription (JAK/STAT) and Phosphatidylinositol 3-kinase/Akt/mammalian target of rapamycin (PI3K/Akt/mTOR) signaling pathways plays a crucial role in the development of acute myeloid leukemia (AML) and chronic myeloid leukemia (CML). Thymoquinone (TQ), one of the main constituents of Nigella sativa, has shown anti-cancer activities in several cancers. However, the inhibitory effect mechanism of TQ on leukemia has not been ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Additionally, TQ inhibited STAT3 phosphorylation in Multiple myeloma cells [ 47 ] and MV4-11 leukemia cells [ 27 ]. Moreover, in our previously published report, we indicated that TQ had reduced the phosphorylation and the protein levels of JAK2, STAT3, and STAT5 protein intensities and phosphorylation in MV4-11 AML cells [ 48 , 49 ]. The findings of this study are also in agreement with previous findings in which TQ treatment reduced the phosphorylation of JAK2 and STAT3, which consequently led to enhanced apoptosis in SK-MEL-28 melanoma cells [ 50 ].…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, TQ inhibited STAT3 phosphorylation in Multiple myeloma cells [ 47 ] and MV4-11 leukemia cells [ 27 ]. Moreover, in our previously published report, we indicated that TQ had reduced the phosphorylation and the protein levels of JAK2, STAT3, and STAT5 protein intensities and phosphorylation in MV4-11 AML cells [ 48 , 49 ]. The findings of this study are also in agreement with previous findings in which TQ treatment reduced the phosphorylation of JAK2 and STAT3, which consequently led to enhanced apoptosis in SK-MEL-28 melanoma cells [ 50 ].…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, the JAK-STAT stimulation in the Helicobacter-pylori-infected gastric epithelial cells was abolished by treatment with α-LA ( Choi et al, 2016 ). Also, TQ was found to induce anticancer effect on myeloid leukemia cells via inhibition JAK/STAT and PI3K/Akt/mTOR pathways ( Al-Rawashde et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primers used for this experiment are listed in Table 1. The protein expression level changes induced by LM1019 in RAW 264.7 cells were assessed using automated capillary western blot assays with the Jess™ system (ProteinSimple, Bio-Techne, Minneapolis, CA, USA) [34][35][36]. RAW 264.7 cells were seeded at a density of 9 × 10 5 cells/well in a 6-well plate and incubated for 24 h at 37 • C in a 5% CO 2 incubator.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%